Kilka uwag o szklanych naczyniach z grodu na Ostrowie Lednickim - Sawicka, Joanna (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2023)
This paper presents the results of an expert study of several glass vessels from an early medieval castle at Ostrów Lednicki. They come from the so-called second church, a single-nave small building erected in the 1060s and destroyed in 1038 or 1039. In its ruins, a collection of high-grade artefacts was discovered, furnishings of the same temple, as well as fragments of glass and fragmentary preserved glass vessels. The three specimens, examined in the laboratory, were made of potassium glass, of the calcium-potassium variety, of the CaO-K2O-MgO-Al2O3-SiO2 type. Interpretation of the analytical results has led to a conclusion that all the vessels could come from a single workshop, attributed to Carolingian and Ottonian workshops in Imperial Germany. Another vessel, discovered in the eastern part of the stronghold and not associated with any of the sacred buildings, has an early date (6th to 9th century). It is believed to be a conical goblet of the Kempston type, made of sodium glass, of the mineral variety, of the Na2O-CaO-Al2O3-SiO2 type, from one of the many Western European workshops.